The Intercultural Socio-Psychological Adaptation of Students in the Polyethnic Educational Space of the Institute of Higher Education - Irina V. Abakumova; Laura T. Kagermazova; Zoia S. Generdukaeva (Rossijskij psihologičeskij žurnal., 2016)
The study is supported the Ministry of Education and Science of the Russian Federation, assignment no. 28.125.2016/НМ The paper discusses the problems of the intercultural socio-psychological adaptation of students studying in Russian institutes of higher education. The implementation of the program of the intercultural socio-psychological adaptation of foreign students is of special relevance. The article describes the logical structure of the program, its conceptual framework, methodological principles, conditions of implementation, and applied methods. The authors (a) developed a foreign student’s portrait, (b) distinguished structural components (social and psychological characteristics) of this portrait, (c) described areas of work on the implementation of the intercultural sociopsychological adaptation of foreign students, and (d) developed recommendations for optimizing the process of adaptation in the educational environment of the institute of higher education. The paper focuses on urgent issues of intercultural communication, linguoculturology, psychology, sociology, and mass communication. To create the necessary prerequisites for possible future activities in the field the unified educational environment in the framework of the Bologna process, the consideration of these problems might be helpful in the effective and competent organization of the intercultural adaptation of foreign students in the unified educational space of the international-oriented institute of higher education, taking into account the rich experience of Kabardino-Balkarian State University named after H. M. Berbekov. The authors offered modern methods of socio-psychological support for the intercultural adaptation of foreign students in the educational space of the institute of higher education. Socio-psychological support for foreign students is an integral, systematically organized activity, which creates favorable conditions for the successful functioning of the person. This is the best way contributing to successful intercultural adaptation of foreign students. Socio-psychological support for foreign students creates conditions for the preservation of the cultural guide of students as representatives of their country, actualization of the existing socio-cultural knowledge, getting the information about the diversity and value of various cultures, increasing the level of intercultural competence, understanding of the necessity of tolerant relation to other cultures and existence of universal values.